STRATEGI PROMOSI DALAM MENINGKATKAN JUMLAH JAMAAH PADA PT BONITA ANUGRAH PRATAMA BUKITTINGGI - Resty Dila Aryanti; Sandra Dewi (BORJUIS: JURNAL OF ECONOMY, 2025)
This study aims to examine the Promotion Strategy in Increasing the Number of Pilgrims at PT Bonita Anugrah Pratama Bukittinggi. The promotional strategy carried out to increase the number of pilgrims at Bonita Anugrah Pratama Bukittinggi by using SWOT analysis so as to increase the number of pilgrims and achieve company targets. The goal of the study is to use the SWOT matrix to identify opportunities, threats, vulnerabilities, and strengths in order to increase the number of pilgrims. The author of this work employed qualitative research as her research approach. This qualitative research method yields descriptive data in the form of observed behaviour and written or spoken language. gathering information by documentation, interviews, and observation. The study's findings, which came from an examination of marketing tactics aimed at boosting pilgrimage, were PT Bonita Anugrah Pratama are to use the S-T Strategy (Strength-Threath). It can be concluded that strengths and threats (ST) have the highest score of 2.94 compared to other strategies. So PT Bonita uses the S-T strategy, which is to optimize existing strengths in order to minimize external threats. From the strategies obtained, it shows that there are 3 promotional strategies to increase the number of pilgrims, namely by increasing advertising promotions through electronic media to build the image of Hajj and Umrah financing products, establishing partnerships to facilitate the process of demonstrating Umrah products and also better understanding the needs of prospective pilgrims both short and long term so as to increase the number of pilgrims